Rural Community Self-support through Mutual Cooperation - Warto Warto (Jurnal Penelitian Kesejahteraan Sosial, 2016)
The research means to reveal rural community self-support implemented through mutual cooperation, including its values inside.Research location is in Sukarena Village, Sentolo Underdistrict, Kulonprogo Regency. Data were gatheredthrough interview, observation, and documentary analysis. The research found that local community still develops selfsupport through mutual cooperation.The self-support model to help community members were through sambatan, rewang, sinoman, self-support through public work, main dailly living job, infrastructures, and religious carrying out together. Self-support was also done through jimpitan, pralenan, credit, and landing-saving as fund collecting. The local community self-support model needs diseminated through a program in the Ministry of Social Affairs to enhance community socialwalfare.